The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1253/circj.70.414
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Plasma Adiponectin Concentrations in Patients With Variant Angina Pectoris

Abstract: Background Plasma adiponectin is decreased in patients with coronary artery diseases, especially in patients with acute coronary syndrome (ACS). However, the correlation between plasma adiponectin and variant angina pectoris (VAP) has not been verified. Plasma adiponectin concentrations between VAP and other coronary artery diseases was compared in the present study. The association between plasma adiponectin concentration and VAP was also investigated. Methods and Results Plasma adiponectin concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…These data support the hypothesis that adiponectin is a key molecule of MetS. 6 As shown in Fig 1, the serum IL-10 level exhibited significant positive correlations with inflammatory markers including hs-CRP [r=0.29 (95% confidence interval (CI); 0.12~0.45)] (Fig 1a), IL-6 [r=0.25 (95% CI; 0.07~0.41)] (Fig 1b), and TNF-[r=0.30 (95% CI; 0.05~0.52)] (Fig 1c). However, the serum levels of IL-10 did not correlate with adiponectin levels [r=0.06 (95% CI; -0.13~0.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These data support the hypothesis that adiponectin is a key molecule of MetS. 6 As shown in Fig 1, the serum IL-10 level exhibited significant positive correlations with inflammatory markers including hs-CRP [r=0.29 (95% confidence interval (CI); 0.12~0.45)] (Fig 1a), IL-6 [r=0.25 (95% CI; 0.07~0.41)] (Fig 1b), and TNF-[r=0.30 (95% CI; 0.05~0.52)] (Fig 1c). However, the serum levels of IL-10 did not correlate with adiponectin levels [r=0.06 (95% CI; -0.13~0.…”
Section: Resultssupporting
confidence: 86%
“…3 Various studies have shown that inflammation also associates with CVD, and that inflammatory markers are predictive of cardiovascular events. 4 Adiponectin, an anti-inflammatory protein, 5 has been demonstrated to be insulin-sensitizing and an anti-atherogenic factor including coronary spasms, 6,7 and is considered a key component of MetS. 8 The serum adiponectin level is known to decrease with an increase in number of MetS components.…”
mentioning
confidence: 99%
“…10 In the clinical setting, APN levels have been significantly and independently related to the development of CAD and acute coronary syndrome and coronary artery spasm. [14][15][16][17][18] In the present study, decreased preprocedural APN levels were associated with long-term MACCE, regardless of the clinical syndrome on admission, which was mostly caused by a trend towards increased incidence of intervention for a new coronary lesion, but not increased incidence of restenosis; however, this trend was not observed if the serum APN levels were adjusted by sex, age, BMI and triglyceride levels. It has been recently reported that plasma APN levels are associated with coronary lesion complexity and that hypoadiponectinemia contributes to coronary plaque vulnerability.…”
Section: Discussionmentioning
confidence: 49%
“…2,3 Previous studies demonstrated that adiponectin levels are decreased in patients with T2DM 4 and CAD, including vasospastic angina. 8,14,15 Individuals with high concentrations of adiponectin are less likely to develop T2DM, 5 and lower adiponectin levels are significantly associated with the future development of myocardial infarction. 9 Although these observations indicate that low levels of adiponectin may contribute to the development of T2DM and atherosclerotic disease, the importance of adiponectin in nondiabetic subjects has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%